Single molecular machines and motors : proceedings of the 1st International Symposium on Single Molecular Machines and Motors, Toulouse 19-20 June 2013 /: proceedings of the 1st International Symposium on Single Molecular Machines and Motors, Toulouse 19-20 June 2013. (2015) - Unknown
No abstract available